Aktivitas Kegemaran Game Online dan Perilaku Siswa Madrasah Ibtidaiyah Hidayatul Mubtadiin Nglaban Loceret Nganjuk - Ahmad Ali Riyadi; Achmad Nur Cholik; Khoiriyah Khoiriyah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This study aims to determine the impact of playing online games on student behavior at MI Hidayatul Mubtadiin Nglaban Loceret Nganjuk for the 2021/2022 academic year. This research is important as a step to develop new rules at school, especially at MI Hidayatul Mubtadiin so that wrong behavior in playing online games is not sustainable in damaging the nation's generation. This type of research is qualitative with the research location at MI Hidayatul Mubtadiin Nglaban Loceret Nganjuk. Data collection was carried out by means of observation, interviews and documentation. The data analysis used descriptive qualitative analysis. The results of this study are, first, there is a correlation between the love of playing online games and student behavior. Second, online games can function as a place to socialize with other players, relieve stress, train motor nerve coordination between eyes and hands. Third, the negative impact of playing online games, is growing a sense of addiction, lack of time control, lying, ignoring the surrounding environment, aggressive behavior and acts of thuggery, misuse of money, impaired health, decreased productivity, isolated from social life, and inculcating the wrong values ​​of life. . Key Word : Online Games, Student Behavior, MI Hidayatul Mubtadiin Nglaban